Hybrid Monoliths for Magnetically‐Driven Protein Separations. (14th April 2014) - Barroso, Telma; Casimiro, Teresa; Ferraria, Ana M.; Mattioli, Fábio; Aguiar‐Ricardo, Ana; Roque, Ana C. A.
<x xml:space="preserve">Abstract</x> Monoliths represent powerful platforms for isolation of large molecules with high added value. This work presents a hybrid approach for antibody (Ab) capture and release. Using mostly natural polymers and clean processes, it is possible to create macroporous monoliths with well‐defined porous networks, tuneable mechanical properties, and easy functionalization with a biomimetic ligand specific for Ab. Magnetic nanoparticles (MNPs) are embedded on the monolith network to confer a controlled magnetic response that facilitates and accelerates Ab recovery in the elution step. The hybrid monolithic systems prepared with agarose or chitosan/poly(vinyl alcohol) (PVA) blends exhibit promising binding capacities of Abs directly from cell‐culture extracts (120 ± 10 mg Ab g−1 support) and controlled Ab magnetically‐assisted elution yielding 95 ± 2% recovery. Moreover, a selective capture of mAbs directly from cell culture extracts is achieved yielding a final mAb preparation with 96% of purity.